Phase‐Change Memory Films: Low‐Dimensional Single‐Cation Formamidinium Lead Halide Perovskites (FAm+2PbmBr3m+2): From Synthesis to Rewritable Phase‐Change Memory Film (Adv. Funct. Mater. 17/2021). (22nd April 2021) - Minh, Duong Nguyen; Nguyen, Lan Anh Thi; Trinh, Cong Tai; Oh, Changjun; Eom, Sangwon; Vu, Thanh Van; Choi, Jinwoo; Sim, Jae Hyun; Lee, Kwang‐Geol; Kim, Jaeyong; Cho, Seong Chan; Lee, Sang Uck; et al.
Abstract : In article number 2011093, Youngjong Kang and co‐workers present a simple in situ quenching‐assisted fabrication technique for FA m +2 Pb m Br3 m +2 films possessing wide dimensional controllability from 1D to 3D structures. The FA m +2 Pb m Br3 m +2 exhibits an unusual (110)‐oriented structure that shows a phase transition to 3D FAPbBr3 under humidity and ultra‐violet light exposure. The phase transition behavior of FA m +2 Pb m Br3 m +2 is utilized for the phase‐change memory films.